Multivalent metal catalysts in Fenton/Fenton-like oxidation system: A critical review - Liu, Yong; Wang, Jianlong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Multivalent metal catalysts in Fenton/Fenton-like oxidation system were reviewed.•Conversion of multivalent metal valence initiated the production of ROS.•Affecting factors of valence conversion of multivalent metal were summered.•Strategies for accelerating the recycle of valence states were summered.•Formation and contribution to decontamination of high-valent metal were discussed. The Fenton/Fenton-like reaction is an advanced oxidation process, which is widely recognized for its efficient removal of recalcitrant organic contaminants. In Fenton/Fenton-like oxidation systems, multivalent metals are important catalysts, such as Fe, Cu, Co, Mn, Ce, Ag, Cr, Ru, W, Mo, V, Ti, etc., which can activate H2O2 to produce reactive oxygen species (ROS) by low-valent metal (Mn+) with reduction properties and high-valent metal (M(n+z)+) with oxidation properties due to the dual roles of H2O2 as reductant and oxidant. Moreover, Fenton/Fenton-like oxidation is a radical reaction process, in which the redox reaction between multivalent metals and radicals may occur. Therefore, the conversion and recycle of valence state of multivalent metals are crucial in the production of ROS and the degradation of organic contaminants. In this review, the recent advances in the conversion and recycle valence states of multivalent metals, including Fe3+/Fe2+, Cu2+/Cu+, Co3+/Co2+, Mn4+/Mn2+, Ce4+/Ce3+, Ru3+/Ru2+, Cr6+/Cr3+, Ti4+/Ti3+, Mo6+/Mo4+ and the like, were systematically reviewed. Firstly, the conversion and influencing factors of valence states of multivalent metals in Fenton processes were introduced; Secondly, the strategies for regenerating low-valent metals were summarized; Thirdly, the formation, determination methods and roles of high-valent metals in contaminant degradation were analyzed and discussed; Finally, the concluding remarks and future perspectives were proposed. This review could provide valuable information for the development of new catalysts of multivalent metals, deepen the understanding of the mechanisms of Fenton/Fenton-like processes and provide a reference for expanding the application of the multivalent metals catalytic Fenton/Fenton-like process in water and wastewater treatment.